Characteristics of the tree cover of Dolores Civil Cemetery and valuation of its environmental services - Benavides Meza, Héctor Mario; García Ponce, Noemí (Instituto de Ecología, A.C., 2023)
The urban forest is commonly associated to city parks and gardens; however, cemeteries are also an important component of this type of forest. Cemeteries have the particularity to be a multifunctional services provider, because in addition to the funerary services that they facilitate, usually they have extensive tree covers that improve the aesthetics, functionality and environmental conditions of the place and the urban surroundings. The characteristics of the tree cover of Dolores Civil Cemetery was never determined before, and no information exists about the structure of the tree cover, the physical and sanitary condition of trees, as well as the environmental services that provide. Dolores cemetery is the oldest of its kind and the largest in Mexico City (112 ha), (and probably of the country), and preserves historic and emblematic sites like the Pantheon of Illustrious Persons. Tree cover diagnostic was implemented through a sampling inventory with 102 sites of 600 m2, where 1051 arboreal individuals (dbh of 5 cm and over), and 30 young trees were recorded from 44 species. Frequency and relative dominance of the species were determined, as well as the mean values in such aspects as height, dbh, basal diameter, crown coverture, physical and sanitary conditions, and maintenance requirements. The entire tree cover characteristics was estimated considering the sampling data, in addition to the environmental services that provide and their economic value. This publication creates a precedent, which could be useful to improve the condition of the tree cover in the cemetery by the personnel in charge.